WEIGHTING THE POSITION & SKILLSET OF PLAYERS IN LEAGUE OF LEGENDS USING ANALYTIC HIERARCHY PROCESS (AHP) - JEREMIAH ANYI, WAN JR (Universiti Malaysia Sarawak, (UNIMAS), 2020)
In this day and age, esports such as League of Legends (LoL) is a popular form of competition using video game, each team consisting of five players. Many researchers have conducted studies in the esports field, however, those that apply quantitative techniques are still scarce. In this project, Analytic Hierarchy Process (AHP) is proposed for weighting position and skillsets of players in LoL. It is hypothesized by the AHP developer that pairwise comparison can be used to derive priority scale through the judgment of experts. A questionnaire is designed to obtain pairwise comparison from players which was then used to develop the prioity scale. The empirical results obtained show the weightage of position and skillset of each player which highlights the important criteria based on their judgment. The results can be used to determine the best players for each position and the skillset required by each player. It is proven that human judgment can be quantified to show important information that can be analyzed. As a lack of experts inhibits this research from obtaining high quality data, it is hoped that future research are able to procure experts for more valuable data.